Advances in Interaction with 3D Environments. (20th October 2014) - Jankowski, J.; Hachet, M.
<x xml:space="preserve">Abstract</x> Various interaction techniques have been developed for interactive 3D environments. This paper presents an up‐to‐date and comprehensive review of the state of the art of non‐immersive interaction techniques for Navigation, Selection & Manipulation, and System Control, including a basic introduction to the topic, the challenges and an examination of a number of popular approaches. We also introduce 3D Interaction Testbed (3DIT) to firstly allow a 'hands‐on' understanding of 3D interaction principles, and secondly to create an open platform for defining evaluation methods, stimuli as well as representative tasks akin to those found in other disciplines of science. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>